2020
DOI: 10.1097/cxa.0000000000000097
|View full text |Cite
|
Sign up to set email alerts
|

A Multilevel Model of Alcohol Outlet Density, Individual Characteristics and Alcohol-Related Injury in Argentinean Young Adults

Abstract: Objectives. Previous research from high-income countries has consistently shown an association between alcohol-related harms and neighborhood characteristics such as alcohol outlet density, but this research has not been extended to middle- and low-income countries. We assessed the role of neighborhood characteristics such as alcohol outlet density, overcrowding and crime rates, and individual characteristics including gender, age, alcohol and marijuana use, and geographic mobility associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“… 16 found that binge drinking once a month was associated with higher odds of self-reported unintentional injury (OR = 1.41 (0.56–4.50)). In retrospective studies, self-reported injuries (intentional and unintentional) have previously been shown to be associated with current alcohol use, 18 , 19 , 41 , 42 , 43 alcohol intake frequency, 12 , 13 , 17 and binge drinking. 14 , 15 , 16 Estimates ranged from OR = 1.10 to 6.0.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 found that binge drinking once a month was associated with higher odds of self-reported unintentional injury (OR = 1.41 (0.56–4.50)). In retrospective studies, self-reported injuries (intentional and unintentional) have previously been shown to be associated with current alcohol use, 18 , 19 , 41 , 42 , 43 alcohol intake frequency, 12 , 13 , 17 and binge drinking. 14 , 15 , 16 Estimates ranged from OR = 1.10 to 6.0.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 , 8 , 9 Yet drinking alcohol at parties is an established social norm among many young people in Western countries, and binge drinking with the main purpose of intoxication is a widespread behaviour, not confined to a limited group of adolescents. 10 , 11 In retrospective studies, current alcohol use, 12 , 13 , 14 , 15 , 16 alcohol use frequency, 12 , 13 , 17 and binge drinking 14 , 15 , 16 have been estimated to increase the odds of self-reported injuries (OR = 1.10–6.0). However, self-reported data on poisonings and injuries may lead to recall bias, and it has been argued that differences in perception between genders, driven by social norms, and willingness to take risks may cause underreporting.…”
Section: Introductionmentioning
confidence: 99%
“…None of the liquor licence bylaws contained regulations on controlling physical availability of alcohol and outlet density a risk factor for high AOD, heavy episodic drinking, alcohol-related harm [9] and crime [33,34]. A participant stated that 'as a LGC if as many as possible can sell alcohol what's our own business, ours is to generate money from them'.…”
Section: Time/day Of Sale and Outlet Densitymentioning
confidence: 99%
“…High levels of alcohol consumption have been associated with increased physical availability of alcohol and high alcohol outlet density (AOD) [9,10]. The World Health Organization SAFER initiative recommends strengthening restrictions on the physical availability of alcohol by regulating hours of sale and AOD [11,12].…”
mentioning
confidence: 99%